Bond Strength and Deflection of Four Types of Bonded Lingual Retainers - Amin Golshah; Shirin Asadian Feyli (International Journal of Dentistry)
Objectives. This study aimed to assess the bond strength and deflection of four types of bonded lingual retainers. Materials and Methods. In this in vitro, experimental study, 160 extracted, mandibular incisors were mounted in acrylic blocks in sets of two and randomized into four groups for bonding of 1.0.010 × 0.026-inch Bond-A-Braid®, 0.012 × 0.027-inch Retanium®TM, 0.038 × 0.016-inch Ortho FlexTech®, and 0.0175-inch three-strand retainer wires; 15 mm of passive wire was adhered to the lingual tooth surface using Transbond XT composite. The shear (SBS) and tensile (TBS) bond strength values were measured. The adhesive remnant index (ARI) score and deflection of wires were also determined under a stereomicroscope. Data were analyzed by the chi-square test and ANOVA. Results. The four groups were significantly different regarding the ARI scores (P<0.05). Significant differences were noted between the three-strand and all other groups in deflection (P<0.05). The Retanium group had significant differences with other groups in peak SBS (P<0.05). A significant difference was found between the Retanium and Ortho Flex groups in break SBS (P<0.05). Significant differences were also reported between the three-strand and all other groups in peak TBS (P<0.05). Conclusion. The Retanium retainer had the maximum SBS, while the three-strand retainer had the maximum TBS. The three-strand and Retanium wires can probably better tolerate intraoral forces and have higher resistance to fracture due to having higher TBS. Also, the three-strand wire had lower deflection rate, which highlights its higher resistance to occlusal forces. Retanium and Ortho FlexTech wires had the most favorable failure modes.